Taqman real-time PCR assay based on ORFV024 gene for rapid detection of orf infection. (June 2013) - Du, Hongyan; Li, Wei; Hao, Wenbo; Liao, Xiaoqing; Li, Ming; Luo, Shuhong
Abstract In this study, a TaqMan real-time polymerase chain reaction (PCR) assay was developed to detect and quantify orf virus (ORFV) DNA in infected cell culture and clinical samples. Primers and probes were designed to amplify an 87 bp fragment DNA based on the sequence of ORFV024 gene encoding an NF-κB inhibitor of orf virus. The assay was highly specific and sensitive for ORFV DNA and no cross-reactions were detected with any other poxviruses; the sensitivity was 5 fg or 15 copies of ORFV genomic DNA. Both intra- (1.490 ± 1.261%) and inter-assay (1.958 ± 0.568%) variabilities were within the acceptable range, indicating the high efficiency and reproducibility of the assay. Further, the assay has shown a relative diagnostic sensitivity and specificity of 100%, when compared to B2L gene-based semi-nested PCR. The assay is simple, rapid, specific and sensitive with a wide potential for rapid field diagnosis of orf in sheep and goats.